The 9th judgment - Patterson, James, 1947- (Patterson, James, 1947- Women's murder club., 2010)
A young mother and her infant child are ruthlessly gunned down while returning to their car in the garage of a shopping mall. The same night, the wife of A-list actor Marcus Dowling is woken by a cat burglar and in just seconds there is a nearly empty safe, a lifeless body, and another mystery that throws San Francisco into hysteria. Before the Women's Murder Club can piece together either case, one of the killers forces Detective Lindsay Boxer to put her own life on the line--but is it enough to save the city?